Efektivitas Model Pembelajaran Problem Solving terhadap Kemampuan Berpikir Kritis Matematika Siswa SD - Ayu Permata Sari; Dosma Mulianti Br Manik; Ellystini Gea; Arif Rahmat Wijaya Gulo; Taruli Marito Silalahi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to examine the effectiveness of the Problem Solving learning model in improving the mathematical critical thinking ability of elementary school students. Through the Systematic Literature Review approach, this study analyzes a number of relevant studies. The results of the study show that the Problem Solving model has significant potential in improving students' critical thinking skills. This model encourages students to be actively involved in the problem-solving process, relate mathematical concepts to real life, and stimulate creativity. However, the implementation of this model requires careful planning, support from various parties, and teacher competency development. Further research is suggested to delve deeper into the factors that affect the successful implementation of the Problem Solving model, as well as develop more specific instruments to measure students' critical thinking skills.